1996
DOI: 10.1111/j.1469-8986.1996.tb02107.x
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related brain potentials and error‐related processing: An analysis of incorrect responses to go and no‐go stimuli

Abstract: Recent research has suggested that there is a component of the event-related brain potential, the error-related negativity (ERN), that is associated with error detection and remedial actions such as error inhibition, immediate error correction, or error compensation. The present experiment used a go/no-go task to define more precisely the functional significance of this component. In this task, an ERN was observed for incorrect responses on go trials (errors of choice) and for responses on no-go trials (errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
178
3
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(198 citation statements)
references
References 22 publications
14
178
3
3
Order By: Relevance
“…Consistent with the functional interaction evidenced between dissociable systems [11] and structures [26] associated with cognitive control, the ERN has been observed to be largest in situations where the recruitment of additional top-down control is required for adaptive task performance [11,21,52,61]. For example, increased ERN magnitude predicts changes in behavior that suggest increased recruitment and implementation of executive control on subsequent trials, including response slowing and increased accuracy following errors [25].…”
Section: Action Monitoring Indicesmentioning
confidence: 67%
“…Consistent with the functional interaction evidenced between dissociable systems [11] and structures [26] associated with cognitive control, the ERN has been observed to be largest in situations where the recruitment of additional top-down control is required for adaptive task performance [11,21,52,61]. For example, increased ERN magnitude predicts changes in behavior that suggest increased recruitment and implementation of executive control on subsequent trials, including response slowing and increased accuracy following errors [25].…”
Section: Action Monitoring Indicesmentioning
confidence: 67%
“…Both the ACC and prefrontal structures have been implicated in additional monitoring. While some workers have suggested that the ACC itself detects problems, errors and conflict in the action system [12,40,8], others emphasize the role of prefrontal structures in evaluating the need for executive control and imply that the ACC is more involved with implementing this control [37,43,19]. Recent successes in dissociating activity in these two regions have supported the latter view [15,18].…”
Section: Creative -Uncreative Contrastsmentioning
confidence: 99%
“…An electrophysiological measure related to error processing is the so-called error-related negativity (ERN; Falkenstein et al, 1991;Gehring et al, 1993), a component of the event-related potential (ERP) that has a fronto-central scalp distribution and peaks about 80 ms after an overt incorrect response (Bernstein et al, 1995;Holroyd and Yeung, 2003;Scheffers et al, 1996). Originally, the ERN was thought to reflect conscious error detection (Bernstein et al, 1995).…”
Section: Introductionmentioning
confidence: 99%